2015
DOI: 10.1021/acs.jafc.5b01351
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic Effects of ArecolineN-Oxide in Oral Potentially Malignant Disorders

Abstract: The metabolites of environmental chemicals play key roles in carcinogenesis. Areca nut is strongly associated with the development of oral potentially malignant disorders (OPMD) or cancer. The main alkaloid in the areca nut is arecoline, which is highly cytotoxic and genotoxic. Arecoline N-oxide, a metabolite of areca nut alkaloids, which has been identified in animal urine, has been shown to induce mutagenicity in bacteria. In this study, it was found that its protein adduct could be detected in oral keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
(50 reference statements)
2
19
0
Order By: Relevance
“…3,4 Also, an in vivo study has demonstrated chromosome breakage. 5 Another report has documented that a related molecule (arecoline N-oxide) increased S100A4 (a member of the metastasis-related proteins in the calcium binding protein family and also used to identify cells of the fibroblast lineage) levels in cultured oral fibroblasts, 6 thereby substantiating the inclusion of this marker protein in this safety assessment study of ours. Also, this protein was found to be elevated in buccal fibroblasts in ex vivo 7 and in vitro studies.…”
Section: Introductionsupporting
confidence: 71%
“…3,4 Also, an in vivo study has demonstrated chromosome breakage. 5 Another report has documented that a related molecule (arecoline N-oxide) increased S100A4 (a member of the metastasis-related proteins in the calcium binding protein family and also used to identify cells of the fibroblast lineage) levels in cultured oral fibroblasts, 6 thereby substantiating the inclusion of this marker protein in this safety assessment study of ours. Also, this protein was found to be elevated in buccal fibroblasts in ex vivo 7 and in vitro studies.…”
Section: Introductionsupporting
confidence: 71%
“…In the past few decades, accumulated studies have demonstrated that areca nuts can induce premalignant and malignant transformation of oral tissues. In animal model studies, areca nut extract (or the ingredient cocktail) can be an effective tumor initiator or promoter and can induce premalignant oral lesions, including submucosal fibrosis 9, 10 and squamous hyperplasia 11-13, or result in malignant transformation 13-16. For example, arecaidine displays a synergistic effect in the 7,12-dimethyl-benz(a)anthracene (DMBA)- induced tumor formation in the cheek pouch of hamster 15.…”
Section: Molecular Pathology Of Areca Nutmentioning
confidence: 99%
“…TNF‐α induced NOTCH1 activation in cultured OSCC cells and regulates the cancer stem‐like cell phenotype and cell invasion (Lee, Ko, Warnakulasuriya et al, ; Yoshida et al, ). IL‐6 and TGF‐β1 stimulation are involved in the fibrotic effect in oral cells (Kuo et al, ; Tsai et al, ). Earlier findings revealed that the arecoline and areca nut ingredients are crucial in the pathogenesis of oral cancer (M. C. Chang et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The cell lysate preparation and western blotting protocols were performed as previously described (Kuo et al, 2015). The primary antibodies used were: anti-phospho-histone H2A.X (Ser139; Cell Signaling Technology), anti-FMO3 (EPR6968; Abcam) and anti-GAPDH (GeneTex Inc., Hsinchu City, Taiwan).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation